Adsorption Characteristics of Phenolic Compounds onto a New Hypercrosslinked Polymeric Resin Containing the 2-Carbonylbenzoyl Group (ZH-01) - Fei Zhenghao; Chen Jinlong; Cai Jianguo; Gao Guandao; Li Aimin; Zhang Quanxing (Adsorption Science & Technology)
A new hypercrosslinked polymeric adsorbent (ZH-01) for the adsorption and removal of phenolic compounds from their aqueous solutions was prepared. Batch kinetic studies and comparisons in adsorption capacities between XAD-4, AM-1 and ZH-01 for 800 mg/l phenol were performed, indicating the advantages of ZH-01 for adsorbing phenol, p -cresol and p -nitrophenol. Both the dynamic and thermodynamic studies concluded that the adsorption of phenol and p -cresol onto ZH-01 involved chemisorption while p -nitrophenol was adsorbed physically onto ZH-01. The latter process demonstrated the homogeneous nature of the surface of ZH-01 adsorbent. Mini-column adsorption studies for phenol on ZH-01 showed that its breakthrough capacity and total capacity were 2.38 mmol/g and 3.05 mmol/g, respectively. Methanol exhibited an excellent performance in desorbing phenol from ZH-01.